Pola Asuh Anak Usia Dini pada Keluarga Buruh Pabrik (Studi Kasus di Desa Kedunglengkong Kecamatan Simo Kabupaten Boyolali) (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to identify various parenting styles or models that are generally applied by parents and the supporting and inhibiting factors of early childhood parenting in factory worker families in Kedunglengkong Village. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of this study consisted of 4 parents and 2 informants. Data validity uses triangulation and the triangulation used is method triangulation. Data analysis used in this research is data collection, data reduction, data presentation, and conclusion making. The results revealed that the parenting process. Broadly speaking, the parenting pattern generally adopted by parents in Kedunglengkong Village is to educate children with positive values, although an authoritarian model is also detected. Supporting factors include parents' high commitment to devote time and attention, while time constraints due to busy schedules are the main obstacle. Based on the evaluation results, the parenting process has gone according to plan.